THE COLLAPSE OF MODERN DEMOCRACY - Barroso de Moraes, George (Revista Gênero e Interdisciplinaridade, 2024)
This scientific article will demonstrate the birth, evolution and crisis of modern democratic regimes. As notorious knowledge, democracy arose from the fall of the monarchical absolutist regime, when human rights appeared accompanied by constitutionalist movements. The evolution was gradual, the result of the social demands that emerged, noting at first the French ideological tripod, namely, freedom, equality and fraternity, reflecting on the social constitutions of social character. It turns out that with the increase of social demands, the state apparatus itself became unable to meet them, despite the existence of social constituent letters enumerating a catalog of human rights. Thus there is the occurrence of the phenomenon of apparent democracy, in which there is a constitutionally foreseen sequence of human rights, together with appropriate legislations, but are not met by the public power, collapsing the system. At the same time, other elements that contribute to the end of democracies are observed, and can point out the partisan political articulations, the search for perpetuation in power, the confidential meetings, the votes for a certain matter and so on that configure what they are what Political scientist Norberto Bobbio defines how the “rules of the game” democratic. Finally, it is appropriate to mention the occurrence of the invisible power of democracy, where not only the subjects hides, but also the content of decisions until the moment they must become public, always having other objectives.